THE INFLUENCE OF AFFILIATE COMMISSIONS, PRODUCT QUALITY, AND AFFILIATE PROMOTION STRATEGY ON ENTREPRENEURIAL INTEREST THROUGH SHOPEE E-COMMERCE PLATFORM - Maria Alisma Dewinta Sari; Titin Hargyatni (Universitas Nusa Cendana, 2026)
This study explores the potential of affiliate marketing as an entrepreneurial opportunity by examining the influence of affiliate commissions, product quality, and affiliate promotion strategies on entrepreneurial interest through the Shopee e-commerce platform. Adopting utilizing a quantitative framework, where primary data was gathered via surveys administered to a sample of 100 participants who had conducted transactions on Shopee and expressed interest in participating in the Shopee affiliate program. The data were analyzed using multiple linear regression. The findings reveal that affiliate commissions have a positive but insignificant effect on entrepreneurial interest. In contrast, product quality and affiliate promotion strategies exert positive and significant effects on entrepreneurial interest. These results suggest that while financial incentives may attract initial attention, perceived product value and effective promotional strategies play a more decisive role in fostering entrepreneurial motivation within affiliate-based digital business models. This study contributes to the growing literature on digital entrepreneurship and provides practical insights for optimizing affiliate marketing programs to encourage entrepreneurial participation. Keywords: Shopee Affiliate Marketing; Affiliate Commissions; Product Quality; Affiliate Promotion Strategies; Entrepreneurial Interest